Gender Representation on North American Ophthalmology Societies' Governance Boards - Bondok, Mostafa; Selvakumar, Rishika; Khan, Muhammad; Bondok, Mohamed S.; Nguyen, Anne Xuan-Lan; Ing, Edsel; Law, Christine (Journal of Academic Ophthalmology, 2023)
Purpose We examined the gender distribution and academic productivity of North American ophthalmology societies' board members.Methods Cross-sectional and retrospective study of board members on American and Canadian ophthalmology societies. In December 2022, data was gathered from society webpages, online archives, and the Scopus database for publication information.Results Of the identified 73 board presidents and 876 other board members, 49 (67.1%) board presidents were men and 24 (32.9%) were women, while 554 (63.2%) other board members were men and 322 (36.8%) were women (p = 0.53). Overall, board members who were men had significantly higher median h-indexes (men vs. women: 10 [interquartile range [IQR] = 22] vs. 7 [IQR = 12], p = 0.03) and median publication numbers (men vs. women: 23 [IQR = 84] vs. 14 [IQR = 52.3], p = 0.01). However, m-quotients (h-index divided by length of academic career) were not significantly different (men vs. women: 0.46 [IQR = 0.74] vs. 0.50 [IQR = 0.55], p = 0.67). Overall, a significant increase in the proportion of women board presidents comparing periods 1942 to 1961 and 2002 to 2021 was observed for all societies combined (3.1% [2/65] to 23.6% [210/888], p < 0.001).Conclusion The fraction of women on the academic boards in North American ophthalmology societies has increased sevenfold over the past 83 years. The gender composition of ophthalmology society boards is consistent with the gender composition of practicing ophthalmologists in the United States. Women in board or society positions have comparable academic output to men. Existing and new efforts to sustain progress in promoting women's representation and leadership opportunities must continue.
Keywords: equity; diversity; health care workforce; medical education and training; ophthalmology